The general's goose Fiji's tale of contemporary misadventure - Robertson, Robert T. 1951- (Australian National University Press, 2017)
His admirers said he was a charismatic leader with a dazzling smile, a commoner following an ancient tradition of warrior service on behalf of an indigenous people who feared marginalisation at the hands of ungrateful immigrants. One tourist pleaded with him to stage a coup in her backyard; in private parties around the capital, Suva, infatuated women whispered 'coup me baby' in his presence. It was so easy to overlook the enormity of what he had done in planning and implementing Fiji's first military coup, to be seduced by celebrity, captivated by the excitement of the moment, and plead its inevitability as the final eruption of long-simmering indigenous discontent. A generation would pass before the consequences of the actions of Fiji's strongman of 1987, Sitiveni Rabuka, would be fully appreciated but, by then, the die had been well and truly cast. The major general did not live happily ever after. No nirvana followed the assertion of indigenous rights. If anything, misadventure became his country's most enduring contemporary trait. This is Fiji's very human story
Keywords: Rabuka, Sitiveni Ligamamada -- 1948-; Geschichte 1987-2016; Staatsstreich; Demokratisierung; Fidschi; Australian; Rabuka, Sitiveni Ligamamada / 1948-; Coups d'état / Fiji; Democracy / Fiji; Fiji / Politics and government; Fiji / History / 20th century; Coups d'état; Democracy; Politics and government; Fiji; 1900-1999; History